A conceptual study on the internal audit effectiveness in malaysian public sector agencies / Nor Raihana Asmar Mohd Noor and Noorhayati Mansor - Mohd Noor, Nor Raihana Asmar; Mansor, Noorhayati (Universiti Teknologi MARA Cawangan Kelantan, 2018)
The recurring issues of corruption, malpractices, poor public service delivery, financial irregularities and fraud always attract widespread attention. Unfortunately, although many policies and regulations have been implemented, these issues are still ongoing which make the efficacy of internal audit in the government sector even more critical than before. However, to date, it is still questionable whether this audit is efficient and effective due to the increasing trend in reported frauds in government departments. The objective of this paper is to examine the scope of audit that is associated with the effectiveness of internal audit. The uniqueness of this paper is to examine a new determinant, namely the practice of whistleblowing, on its effect in mediating the effectiveness of internal audit. The usefulness of this paper is to overcome the increasing rate of fraud in Malaysian public sector and encourage the whistleblowing practice in public sector agencies. It is undeniably very important because the public generally prefers to remain silent, thereby escalating the issues of fraud. The public may be intimated that if they file a complaint especially towards someone more superior, or a highly-regarded person, retaliatory actions may be taken against them and this could destroy their career. Moreover, the public also believes that it is better to keep quiet rather than suffer any consequences or social pressures. The findings are expected to enhance the government initiatives in fighting frauds and corruptions through effective internal audit practice and improving the internal audit. The effect of whistle blowing practice will provide further evidence to strengthen the internal control system and practices and improve the public sector accountability and transparency